Tricuspid valve infective endocarditis in a non-IVDU patient with atopic dermatitis. Issue 7 (24th July 2020) - Woodun, Heerani; Bouayyad, Sarah; Sahib, Sura; Elamin, Nadir; Hunter, Steven; Al-Mohammad, Abdallah
Abstract: A 29-year-old male, with chronic atopic dermatitis (AD), presented with a 2-week history of fatigue, pyrexia and weight loss. Examination showed eczematous patches with lichenified papules, erosions on the right shin and a new murmur. Blood cultures isolated methicillin-sensitive Staphylococcus aureus . Transthoracic echocardiography showed vegetation on the tricuspid valve (TV) that was adherent to the septal leaflet. He was treated for infective endocarditis, attributed to poorly controlled AD, with intravenous Flucloxacillin. Due to ongoing sepsis and pulmonary septic emboli, Clindamycin was added. He underwent TV repair; the septal leaflet was excised, and the remnant two leaflets were brought together with a ring. His patent foramen ovale was closed. His skin was treated with topical steroids and emollients. Right-sided endocarditis of an intact TV is uncommon in a non-intravenous drug user. Therefore, this novel case portrays the importance of aggressively managing AD as it is a risk factor for significant systemic infections.